Multi-tissue transcriptome analyses identify genetic mechanisms underlying neuropsychiatric traits - Gamazon, Eric R.; Zwinderman, Aeilko H.; Cox, Nancy J.; Denys, Damiaan; Derks, Eske M. (Nature genetics, 2019)
The genetic architecture of psychiatric disorders is characterized by a large number of small-effect variants 1 located primarily in non-coding regions, suggesting that the underlying causal effects may influence disease risk by modulating gene expression 2 – 4 . We provide comprehensive analyses using transcriptome data from an unprecedented collection of tissues to gain pathophysiological insights into the role of the brain, neuroendocrine factors (adrenal gland) and gastrointestinal systems (colon) in psychiatric disorders. In each tissue, we perform PrediXcan analysis and identify trait-associated genes for schizophrenia ( n associations = 499; n unique genes = 275), bipolar disorder ( n associations = 17; n unique genes = 13), attention deficit hyperactivity disorder ( n associations = 19; n unique genes = 12) and broad depression ( n associations = 41; n unique genes = 31). Importantly, both PrediXcan and summary-data-based Mendelian randomization/heterogeneity in dependent instruments analyses suggest potentially causal genes in non-brain tissues, showing the utility of these tissues for mapping psychiatric disease genetic predisposition. Our analyses further highlight the importance of joint tissue approaches as 76% of the genes were detected only in difficult-to-acquire tissues. Multi-tissue transcriptome analyses using PrediXcan identify numerous trait-associated genes for schizophrenia, bipolar disorder, attention deficit hyperactivity disorder and broad depression, and highlight potentially causal genes in non-brain tissues.